Hyalosira (Diatomeae: Grammatophoraceae) from Florida Keys, U.S.A., Including Two New Species with Consistent Ornamentation - Christopher S. Lobban (Diversity)
Diatoms are the most numerous of algae and scanning electron microscopy continues to reveal ever-increasing diversity. Two new species of Hyalosira from Florida add new characters distinguishing species in this recently redefined genus: H. ornata sp. nov. from Florida Bay has consistent and elaborate ornamentation on both valves and undulate valve margins; H. sertifera sp. nov., from the Atlantic coast of Key Largo, has a thick, consistent, garland-like ring of cristae on only one valve; the former species has deep septa on all copulae except the valvocopula, the latter shallow septa or none on the copulae. Hyalosira hesperia was also found in the Atlantic sample; this is the first record outside the Mediterranean. The number of species known from SEM is now twelve, including four with septa, a diversity potentially useful in exploring outstanding questions of septum function; a key to these species is appended.